2021
DOI: 10.1186/s12879-021-06298-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection by a rare pathogen Cedecea neteri in a pregnant female with Polyhydramnios: rare case report from UAE

Abstract: Background Cedecea neteri is a gram-negative, oxidase-negative bacillus, a rare pathogen. Few reports are emerging globally about its antimicrobial resistance pattern especially in immunocompromised individuals with comorbidities. Case presentation In this paper, we report the first case of C. neteri causing urinary tract infection in a pregnant woman at a specialty care hospital in the Northern Emirates of Ras al Khaimah, UAE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Amycolatopsis is an important source of several bioactive natural products with good antibiotic-producing potential [ 52 ]. Cedecea is a rare conditionally pathogenic bacterium that usually proliferates in immunocompromised patients [ 53 ]. Lactase activity is determined by gene expression, but not all lactase enzymes express activity.…”
Section: Discussionmentioning
confidence: 99%
“…Amycolatopsis is an important source of several bioactive natural products with good antibiotic-producing potential [ 52 ]. Cedecea is a rare conditionally pathogenic bacterium that usually proliferates in immunocompromised patients [ 53 ]. Lactase activity is determined by gene expression, but not all lactase enzymes express activity.…”
Section: Discussionmentioning
confidence: 99%
“…These species, have been reported to be found across many soil and aquatic habitats, and are associated with plants, insects, and human gut microbiome (Dalamaga and Vrioni 2011). There have been number of reports which discuss about its pathogenicity, mostly addressed in immunocompromised individuals (Thompson and Sharkady 2021; Ahmad et al 2021;Ginn et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that Cedecea encodes genes for antimicrobial resistance, but the exact proteins encoding such genes are not known (Thompson and Sharkady 2021;Notter et al 2022;Ginn et al 2018) In 2015, a previously undiscovered species from the genus Cedecea, specifically identified as Cedecea neteri SSMD04, was first isolated from pickled mackerel sashimi (Tan et al 2015). C. neteri SSMD04 is a gram-negative, bacillus that is found relatively rare in nature, but was recently identified as the infectious agent of a urinary tract infection in a pregnant female with polyhydramnios (Ahmad et al 2021). Evidence of its infection in the bloodstream of a person with systemic lupus erythematosus (SLE) has been reported in the past (Aguilera et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In immunocompromised hosts, such as those with chemotherapy-induced neutropenia, cystic fibrosis, or severe burns, as well as those receiving intensive care, Infections may be associated with a high rate of deaths (Markou and Apidianakis, 2014). Cedecea is a rare but increasingly significant pathogen, it is difficult to treat infections caused by Cedecea species that contain antibiotic resistance genes (Ahmad et al, 2021). The Centers for Disease Control and Prevention (CDC) identified Cedecea as a new genus in the family Enterobacteriaceae, formerly designated as CDC enteric group 15, and the organism was later named Cedecea from the letters CDC (Akinosoglou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%